Paraquat-associated Severe Acute Kidney Injury—Study from India - Manjusha Yadla; K. Manu; K.V. Anupama; B. Rajasekhar (Journal of Renal and Hepatic Disorders)
To analyze the outcomes of severe acute kidney injury in patients with paraquat ingestion. This retrospective analysis of case records was done in our institute, a tertiary care government teaching hospital, over a period of 4 years. Of the total 1310 acute paraquat poisonings during this period, severe acute kidney injury (AKI), referred for nephrology management was observed in 60 patients. Common symptoms at presentation include vomiting, oral ulcers, and abdominal pain. Oliguric AKI was present in 26%. Need for renal replacement therapy was observed in 95% of the cases. Mortality was observed in 38 of the 60 patients (68%). Factors associated with mortality on Cox regression analysis include amount of consumption. Estimated duration of survival on analysis curves was 8 days in 50% after admission and 15 days after consumption in 50%. Paraquat poisoning is associated with grave outcomes of morbidity and mortality. Severity of AKI is significant in this poisoning. Amount of consumption, latency of referral play a major role in outcomes.